A National Comparative Study Regarding Rural Special Education Delivery Systems Before and After Passage of PL 94-142 - Helge, Doris; Murray State Univ., KY. Center for Innovation and Development ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Despite problems, extraordinary progress has been made to provide a free and appropriate public education for handicapped students in rural America. A study of 75 school districts and cooperatives in 17 states revealed significant improvements in programs and services offered and types and ages of exceptional students served. Achievements included a 92% average increase in the number of handicapped students identified and served, percentage changes of up to 1,525% in services before and after implementation of PL 94-142, and establishment of procedures for due process and parental involvement. Services previously nonexistent such as physical and occupational therapy and programs for severely handicapped students were enacted in many small schools at no cost to parents of handicapped students. A preponderance of data indicated that major hindering factors were teacher recruitment and retention problems and funding and staff inadequacies. Attendant cultural, geographic, and climatic variables inhibited service delivery to a lesser degree. Although significant challenges remain, the Education of All Handicapped Children Act has clearly initiated efforts toward full services for rural handicapped students. Appendices contain the data collection instruments and a cost analysis model for rural district service delivery systems. (Author/JH)
Sponsoring Agency: Bureau of Education for the Handicapped (DHEW/OE), Washington, DC.
Contract Number: G007801686.
ERIC Note: Light print may not reproduce clearly.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Comparative Analysis; Cost Effectiveness; Delivery Systems; Due Process; Educational Change; Exceptional Persons; Federal Legislation; Mainstreaming; Parent Participation; Program Evaluation; Questionnaires; Rural Schools; Small Schools; Special Education; Special Education Teachers; Teacher Recruitment; Education for All Handicapped Children Act -- Impact Studies; Reports, Evaluative